Gypsum and green manuring influence soil sodicity and mustard productivity under semi-arid conditions of Rajasthan - Saraswat, Pankaj Kumar; Chaudhary, Banshidhar; Rathore, S.S.; Bhati, Ashu Singh (Annals of Agricultural Research, 2016)
Three on farm-testing (OFTs) on green manuring for introduction and assessment of their effects onmustard production and sodic soil quality were conducted at farmer's field during 2011-12 to 2013-14 in selected villages of Niwai and Todaraisingh Tehsil of Tonk district. OFT treatments comprisedas T1: farmer's practice-FP, T2Gypsum 50% GR + RDF + Green gram, T4GR + RDF + Crotolaria as technological interventions. Results of OFT's revealed that technologicalinterventions T4whereas T3(Gypsum 50% GR + RDF + Green gram) could registered significantly higher yield onlyover T1. Higher monitory gains in terms of benefit cost ratio (B:C ratio) were also achieved in T4treatments. Inclusion of green manuring (GM) particularly Sesbania and Crotolaria along withT5Gypsum use resulted in to remarkable reduction in pH, EC and BD and improvements in organiccarbon, available NPK and micronutrients in sodic soils in Tonk district of Rajasthan. Introductionof green manuring in kharif fallow fields reserved for mustard sowing in rabi season got fitted inprevailing cropping system.: Recommended POP for mustard (Gypsum 50% GR + FYM+ RDF), T3:: Gypsum 50% GR + RDF + Sesbania and T5: Gypsum 50%and T5registered significantly higher mustard yield even over FP and POP treatmentsand